POTRET MANUSIA INDONESIA DALAM CERPEN â€œDERABATâ€ KARYA BUDI DARMA Kajian Strukturalisme Genetik - Anas Ahmadi (Universitas 17 Agustus 1945 Surabaya, 2010)
Abstract.Â This article discusses â€œDerabatâ€ written by Budi Darma using sociology of literature and Genetic Structuralist teories. It focuses on the writerâ€™s pont of view in protraiting Indonesian people. The analysis shows that social political condition of Indonesia Â in the writerâ€™s point of view (Budi Darma) is in a mass. It manifest through the conflicts that emerge among the political etiles and through the decrease of social participant of the â€œordinaryâ€ class of Indonesian society.Key words: sociology of literature, genetic structurist